2016
DOI: 10.18043/ncm.77.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Enrollment and Racial Disparities in Cancer Treatment Clinical Trials in North Carolina

Abstract: Background Clinical trials provide access to innovative, quality cancer treatment. Simultaneously, broad access helps ensure trial inclusion of heterogeneous patient populations, which improves generalizability of findings and development of interventions that are effective for diverse populations. We provide updated data describing enrollment into cancer treatment trials in North Carolina. Methods For 1996 to 2009, person-level data regarding cancer clinical trial enrollment and cancer incidence were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…Another marked disparity in treatment between rural and urban cancer patients concerns recruitment into clinical trials. A study evaluating treatment trials in North Carolina found that the rate of enrollment was higher among urban populations than among the most rural populations (2.4% vs. 1.5%) (12). The authors suggested that despite initiatives like the Community Clinical Oncology Program (CCOP) and the National Community Cancer Centers Program (NCCCP) to enhance access to cancer trials and increase enrollment of diverse patients, rural residents still face access barriers to trial participation (12).…”
Section: Introductionmentioning
confidence: 99%
“…Another marked disparity in treatment between rural and urban cancer patients concerns recruitment into clinical trials. A study evaluating treatment trials in North Carolina found that the rate of enrollment was higher among urban populations than among the most rural populations (2.4% vs. 1.5%) (12). The authors suggested that despite initiatives like the Community Clinical Oncology Program (CCOP) and the National Community Cancer Centers Program (NCCCP) to enhance access to cancer trials and increase enrollment of diverse patients, rural residents still face access barriers to trial participation (12).…”
Section: Introductionmentioning
confidence: 99%
“…A landmark systematic review of studies related to research consent revealed that Blacks were generally as willing as any others to take part in RCTs, that remarkably few studies reported their consent rates by race and ethnicity and that the heterogeneity in how consent rates were reported prevented comparisons across studies. 3 On the other hand, there are studies that document racial and ethnic disparities in health research participation [4][5][6][7] and a recent systematic review of barriers and facilitators to minority participation in research identified mistrust, stigma, and competing demands as common barriers. 8 Unfortunately, there is a paucity of pediatric data on research consent and enrollment and even fewer studies examining this issue in critically ill children.…”
mentioning
confidence: 99%
“…Disparities among cancer treatment clinical trial participants are well recognized [[11], [12], [13]]. Some studies have examined disparities within specific cancer types and identified the need for accruing representative patients within a tumor type [9].…”
Section: Introductionmentioning
confidence: 99%